Is core money growth a good and stable inflation predictor in the euro area? - Kai Carstensen (Kiel Institute for the World Economy (IfW), 2007)
In this paper, it is analyzed whether core money growth helps to predict future inflation in a useful and reliable way. Using an out-of-sample forecasting exercise and a stability analysis, it is shown that core money growth carries important information not contained in the inflation history, that its inclusion in a forecasting model can increase the forecasting accuracy, and that it has had a strong and stable long-run link to inflation over the last decades. A particularly promising forecasting model at all horizons is the one proposed by Gerlach (2004) that includes the inflation gap, the difference between core money growth and core inflation, and the output gap. This model has a very good track record, exhibits stable parameters over both the pre-EMU and the EMU era. What makes it appealing from a more theoretical perspective is that it relies on the stable long-run relationship between money growth and inflation.
Keywords: E58; E47; 330; Forecasting; core money growth; stability; filter; Geldmenge; Inflationsrate; Prognoseverfahren; Zeitreihenanalyse; Schätzung; Inflation; Europäische Wirtschafts- und Währungsunion; EU-Staaten